Safety Assessment of Glucose-Lowering Drugs and Importance of Structured Education during Ramadan: A Systematic Review and Meta-Analysis - Rashmi Shiju; Ayesha Akhil; Smitha Thankachan; Jaakko Tuomilehto; Monira Al Arouj; Abdullah Bennakhi (Journal of Diabetes Research)
Background. Ramadan is the sacred month of the Islamic Hijri (lunar) calendar, and during this entire month, healthy adult Muslims abstain from eating and drinking from dawn to sunset. Muslims with Type 2 Diabetes Mellitus (T2DM) who choose to fast during Ramadan encounter major risks such as hypoglycemia, hyperglycemia, diabetic ketoacidosis, dehydration, and thrombosis. Although patients with poor glycemic control and on multiple insulin injections are at high risk and exempt from fasting, many still insist on it. Thus, healthcare professionals play a pivotal role in managing diabetes-related complications in patients who fast during Ramadan. However, there is a lack of standard guidelines to be followed in association with structured education and administration of drugs and dosage. Therefore, we performed a systematic review and meta-analysis of the literature to determine the safety and efficacy of different classes of drugs and the importance of structured education during Ramadan. Methods. In this review, an extensive PubMed search was performed to obtain literature on T2DM patients who fast during the month of Ramadan until the year 2020. Preference was given to fully downloadable articles. The articles were extracted based on the eligibility criteria. The extracted data were analyzed using Review Manager software version 5.3. Results. A total of 32 articles were included for the review and 7 studies for meta-analysis. Majority of the studies demonstrated the importance of structured education either as a group session or as a one-on-one session with the healthcare professionals in preventing diabetes-related risks during Ramadan. As far as glucose-lowering drugs are concerned, DPP-4 inhibitor combined with metformin remains the drug of choice for T2DM patients who fast during Ramadan. The newer class of glucose-lowering agents appear to lower the risk of hypoglycemia in comparison with sulphonylureas, while among sulphonylureas gliclazide is relatively safe. The meta-analysis indicates that DPP-4 inhibitors would significantly reduce the risk of hypoglycemia as compared to sulphonylurea (odds ratio=0.38, 95% CI: 0.26 to 0.55, p<0.00001). Conclusion. The results of our systematic review show that structured education and counselling by healthcare professionals can be an effective tool in preventing complications associated with fasting during Ramadan in people with T2DM. Additionally, the safest class of oral glucose-lowering drugs preferred during Ramadan fasting in T2DM patients is DPP-4 inhibitors.